2012
DOI: 10.1038/ijos.2012.36
|View full text |Cite
|
Sign up to set email alerts
|

Angiosarcoma of the scalp diagnosed by the presence of neck inflammation: a case report

Abstract: Angiosarcoma is an uncommon malignancy, which spread out from the endothelial cells of vessels. Scalp angiosarcoma with cervical lymph node metastasis is particularly rare. This article describes a rare case of angiosarcoma of the scalp, presenting as neck inflammation. Imaging procedures such as computed tomography (CT), magnetic resonance image (MRI) and ultrasonography (US) were not sufficient to diagnose this case. A needle biopsy provided an effective and accurate diagnosis of cervical lymph node metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Using mutational signature analysis to understand the possible origins of tumor hypermutation, we 7 found that all 9 of these HNFS samples with high TMB had a dominant mutational signature representing damage from ultraviolet (UV) light (COSMIC Signature 7) 25 Figure 6D). The fact that high TMB and a concomitant dominant mutational signature of UV light exposure occurs uniquely in HNFS AS suggest a common etiologic and genomic basis for HNFS AS, which is an AS subtype accounting for nearly 60% of AS cases 26,27 .…”
mentioning
confidence: 99%
“…Using mutational signature analysis to understand the possible origins of tumor hypermutation, we 7 found that all 9 of these HNFS samples with high TMB had a dominant mutational signature representing damage from ultraviolet (UV) light (COSMIC Signature 7) 25 Figure 6D). The fact that high TMB and a concomitant dominant mutational signature of UV light exposure occurs uniquely in HNFS AS suggest a common etiologic and genomic basis for HNFS AS, which is an AS subtype accounting for nearly 60% of AS cases 26,27 .…”
mentioning
confidence: 99%
“…In this case, the patient underwent lung biopsies, twice, and both did not indicate a malignant tumor. We assumed that the error in pathological results were owing to fewer samples obtained by puncture biopsy and various degrees of inflammation around the lesions probably, which might have affected the correct diagnosis ( 28 , 29 ). Therefore, tissue samples could be obtained by multi-site or video-assisted thoracoscopic biopsies, which could effectively improve the positivity rate of biopsy.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Several reports have indicated that docetaxel and paclitaxel have demonstrated improved disease-free survival and may be effective in preventing or treating lung metastases. 2 5 18 19 20 21 However, dose-limiting side effects can pose an issue. Our results also suggest a role for this combined-modality approach as our sole survivor of positive surgical margins was treated using neoadjuvant chemotherapy (weekly paclitaxel) and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%